The Monte's 'Monte': The Early Supporters of Florence's Monte di Pieta - Menning, Carol Bresnahan (The sixteenth century journal, 1992)
Monti di pieta, charitable civic pawnshops offering loans against pawns at low interest rates, required an accumulation of capital, or a "monte," to undertake their charitable lending. The Florentine establishment, a product of the unusual cooperation between its Franciscan advocates and the Dominican mystic Savonarola, expected to amass its "monte" from donations and free loans offered by "inspired persons." The sketchy research on who provided this capital has suggested that significant support for the monte di pieta in its early years came from members of the populo minuto. A closer examination of the evidence reveals instead that the pawnshop's support came from a few members of the city's patriciate, corporate groups, fines resulting from lawsuits, and resources delegated to it by the Commune.